2012
DOI: 10.1038/onc.2011.586
|View full text |Cite|
|
Sign up to set email alerts
|

Chk1 phosphorylation of Metnase enhances DNA repair but inhibits replication fork restart

Abstract: Chk1 both arrests replication forks and enhances repair of DNA damage by phosphorylation of downstream effectors. While there has been a distinguished effort in identifying effectors of Chk1 activity, there are still mechanisms of its activities that are yet to be identified. Metnase/SETMAR is a SET and transposase domain protein that promotes both DNA double strand break (DSB) repair and re-start of stalled replication forks. In this study, we show that Metnase is phosphorylated only on Ser495 (S495) in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 39 publications
2
57
0
Order By: Relevance
“…We previously found that the unphosphorylated Metnase species is far better at restarting replication forks than the phosphorylated species, implying that Chk1 activity inhibited Metnase’s fork restart capability [8]. These data here, together with that previous report, suggest a layer of complexity in Chk1 signaling not currently appreciated.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…We previously found that the unphosphorylated Metnase species is far better at restarting replication forks than the phosphorylated species, implying that Chk1 activity inhibited Metnase’s fork restart capability [8]. These data here, together with that previous report, suggest a layer of complexity in Chk1 signaling not currently appreciated.…”
Section: Resultssupporting
confidence: 68%
“…We discovered that Metnase is phosphorylated at S495 in response to DNA damage by Chk1 [8]. Phosphorylation of Metnase increased its DNA DSB repair capacity, but decreased its replication fork restart activity.…”
Section: Resultsmentioning
confidence: 99%
“…The increase of H3K36me2 at I-SceI-induced DSB site is mediated by recruiting Metnase (also SETMAR) and is required for NHEJ repair [47], which is in agreement with the role of Metnase in NHEJ [77,78]. The recruitment of Metnase relies on phosphorylation of Ser495 by Chk1, but not by ATM [79]. We also found that dissociation of H3K36me2-specific demethylase JHDM1a/KDM2A with chromatin is also critical for this process, and this dissociation between KDM2A and chromatin is a result of ATM-dependent phosphorylation on Thr632 [76].…”
Section: H3k36 Methylationsupporting
confidence: 62%
“…Because SETMAR has been reported to act specifically at sites of DNA damage, it may be that methylation only occurs on a small fraction of the total substrate pool, perhaps to shut down splicing at sites of DNA damage (4). It could also be that SETMAR activity depends on upstream activities, such as phosphorylation by Chk1 (34).…”
Section: Discussionmentioning
confidence: 99%